2003
DOI: 10.2320/matertrans.44.239
|View full text |Cite
|
Sign up to set email alerts
|

Change in Vickers Hardness and Substructure during Creep of a Mod.9Cr-1Mo Steel

Abstract: In order to investigate the structural degradation during creep, interrupted creep tests were conducted of a Mod.9Cr-1Mo steel in the range of stress and temperature from 71 to 167 MPa and 873 to 923 K. The change of hardness and tempered martensitic lath width were measured in grip and gauge parts of interrupted specimens. The lath structure was thermally stable in static conditions, however, it was not stable during creep and the structural change was enhanced by creep strain. The relation between the change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Then, we separately discuss the possible mechanism in the two regions in terms of the applied stress below and above~120 MPa. In the lower stress region, the work by Endo et al [14] suggests that the coarsening mechanism by the applied stress was not activated and we thus consider that the martensitic structure should be stabilized by the precipitates, leading to the steady state of creep deformation. While the coarsening of the fine precipitates progressively occurs, there is a certain duration of the steady state; this is because there should be a sufficient amount of fine precipitates in the initial microstructure.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Then, we separately discuss the possible mechanism in the two regions in terms of the applied stress below and above~120 MPa. In the lower stress region, the work by Endo et al [14] suggests that the coarsening mechanism by the applied stress was not activated and we thus consider that the martensitic structure should be stabilized by the precipitates, leading to the steady state of creep deformation. While the coarsening of the fine precipitates progressively occurs, there is a certain duration of the steady state; this is because there should be a sufficient amount of fine precipitates in the initial microstructure.…”
Section: Resultsmentioning
confidence: 92%
“…The Gr.91 steel exhibits long-term stability of the martensitic structure owing to fine precipitates introduced by tempering [11]. According to previous works [12][13][14], however, the martensitic structure is not necessarily stable and the lath boundary of the martensitic structure migrates under an applied stress in creep deformation. For example, Endo et al [14] claimed that the dislocations composing the subgrain boundary like the lath boundary, which are pinned by the fine precipitates, can migrate by unpinning under an applied stress above a certain level and estimated that the stress necessary for unpinning is approximately 100 MPa.…”
Section: Resultsmentioning
confidence: 97%
“…Major variation in lath width and precipitate size was noted in samples tempered at 740°C as compared to 760°C and 780°C. This difference can be attributed to the creep stress assisted boundary migration [30] which is a precursor to the observed changes in the initial microstructure, resulting in high rupture life. However, in case of 780°C tempering, the initial microstructure did not allow any significant variation in lath width and precipitate size resulting in less rupture times.…”
Section: Microstructural Changes During Creepmentioning
confidence: 93%
“…It was suggested that the changes in decomposed profiles due to ageing might reflect the dislocation density conditions and precipitation of M 23 C 6 , etc. [48].…”
Section: Measurement Of Lattice Defect Response To Creep Degradationmentioning
confidence: 99%